Optimization of Producing Zein Clove Leaf Essential Oil Nanoparticles for Their Antioxidant Activities - Refilda Refilda; Mutia Ramadani; Ainun Nasution; Imelda Imelda; Yefrida Yefrida; Irmanida Batubara (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2024)
Essential oils are often also referred to as flying oils produced by plants and usually volatile essential oils at room temperature, one of the essential oils with many uses is clove leaf essential oil (Syzygium aromaticum L). Zein-essential oil nanoparticles were prepared by varying the concentration of clove oil (0, 2, 4, 6, 8, and 20 mg/mL) added to 1.5 mg/mL zein and 1 ml tween 20 and sonicated for 20 minutes. The antioxidant activity of the zein-essential oil nanoparticles formed was tested using the DPPH method. The best antioxidant activity was found in the addition of clove leaf essential oil 8 mg/mL with a percentage of inhibition of 71.13%. Characterization test with a laser beam where the amount of light scattered by the solution. Chemical component analysis using Gas Chromatography Mass Spectrophotometry (GC-MS) showed the presence of 32 compounds with three main compounds, namely trans-?-caryophyllene (46.69%), chavibetol (25.80%) and - humulene (10.84%).